Ultrastructure of STH cells in the pars distalis of the hypophysis of mice bearing transplanted hepatomas - Badrán, Amado F. (1971)
An electron microscopic analysis was performed on the pars distalis of the hypophysis of mice bearing transplanted hepatomas. Normal mice served as controls. In animals bearing a fast growing as well as in those bearing a slow growing hepatoma, the STH cells presented changes indicating increased release and synthesis of its secretory product. These changes can be summarized as follows: 1) Increased number of granuledepleted STH cells which were very irregular in size and shape. 2) Very irregular and sometimes bizarre nuclei. 3) Plasma membranes irregular and convoluted. 4) Increased quantity of endoplasmic reticulum which appeared sometimes dilated and contained material of varying electron density. 5) Abundant, irregular and frequently ramified mitochondria. 6) Hypertrophic Golgi system with increased number of microvesicles. 7) Increased number of large lysosomes of different type. 8) Increased number of fat droplets.